Azyumardi Azra : Pembaruan Pemikiran dan Kelembagaan Pendidikan Islam di Indonesia - Wahyuddin Noor (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
As a scholar, Azyumardi Azra is one of the many reformers of Islamic education in Indonesia. Islamic education, according to Azra, needs to develop a dual approach strategy with the aim of integrating short-term situational approaches with a long-term conceptual approach. Changes in Islamic education can be done by changing thinking and institutions. This change of thought and institutions is a prerequisite for the rise of the Muslims in modern times. Renewal of Islamic education thought Azyumardi Azra, including: a). Modernization of Islamic education; b). Democratization of Islamic education. In the field of institutionalism, Azra was also known as an activist or practitioner of reforming Islamic education institutions. During his leadership, IAIN Syarif Hidayatullah Jakarta experienced a change in status to UIN Syarif Hidayatullah Jakarta, truly an achievement that had never been achieved in the previous era.